Prevalência e relação de fatores emocionais e clínicos em pacientes com discopatia degenerativa - Amaral, Vivian (2010)
OBJECTIVES: to describe the psychosocial conditions, at the time of surgical indication, of patients with chronic low back pain caused by degenerative disc disease. METHODS: in a series of 32 cases of degenerative disc disease elective surgery, a psychological evaluation was performed before the surgery. In this evaluation, socio-demographic data were collected: gender; age; present working status; occurrence of withdrawal due to disability; and clinical-psychological data: pain; physical restraint; use of psychiatric medication controlled; degree of anxiety; degree of depression; degree of hopelessness; expectations before the surgical goal. RESULTS: the group was composed of 13 women and 14 men, mean age of 44.3 years old (23 to 65 years). The parameters of pain and physical restraint were compared to cases usually indicative of surgery, indicating no peculiarity in the studied group. We demonstrated a high and correlated prevalence of psychological changes in patients: 50% of depression, 54% of anxiety and 22% of hopelessness. Furthermore, it was possible to show high rates of absence from work due to physical disability and relation to the presence of anxiety and/or depression with cases in which expectations were misleading according to the surgical objective. CONCLUSIONS: chronic low back pain is accompanied by clinical pictures of pain and psychological disorders such as anxiety, depression and hopelessness. These parameters indicate the need for pre-surgical psychological evaluation and posterior follow-up, aiming at the rehabilitation of the patient.